The use of water‐filled tree holes by vertebrates in temperate forests. Issue 1 (15th March 2021) - Kirsch, Jennifer‐Justine; Sermon, Jana; Jonker, Marlotte; Asbeck, Thomas; Gossner, Martin M.; Petermann, Jana S.; Basile, Marco
Abstract : Water‐filled tree holes (WHs), commonly referred to as dendrotelmata, develop when water accumulates in cavities related to tree architecture or in rotten parts of the tree. These structures can occur in forest ecosystems and may represent essential microhabitats in the life cycle of various animal species. WHs form temporary microhabitats during wet periods and sometimes sustain water throughout dry seasons. Research on the use of WHs by organisms mainly focuses on invertebrates developing in these while vertebrates are rarely mentioned. A literature search on the use of WHs by vertebrates revealed that attention has been given only to vertebrates in tropical and subtropical systems, mostly to groups with aquatic stages, such as amphibians. To fill the knowledge gap on the use of WHs by vertebrates in temperate forests, we conducted a camera study in three sites across Germany. We identified a total of 28 vertebrate species including 11 mammal, 17 bird and one amphibian species using the WHs. The recorded videos showed that vertebrates use the WHs mainly for nutrition and hydration. With an expected future increase in frequency and intensity of dry spells in central Europe, these microhabitats may sustain healthy forest ecosystems by providing resources for wildlife. Reliable, updated data about the importance of WHs for vertebrates is required to urge forest managers and stakeholders to enforce the preservation of these microhabitats.